Age and household solid waste arising in suburban Malaysia: a statistical approach - Irwan, Dani; Basri, Noor Ezlin Ahmad; Watanabe, Kohei; Ahmed, Ali Najah (Springer, 2022)
An ageing society could be construed as a socioeconomic disaster as it entails many multi-layered complications across many aspects essential to the running of an efficient and sustainable city. This paper aims to examine the relationship between age and the rate of household solid waste (HSW) generation per capita from households in selected residential areas of the suburban Malaysian townships of Bandar Baru Bangi, Putrajaya and Kajang. Primary HSW data arising was collected directly via door-to-door bin sampling method from an initial sample of 423 individual households during pre-determined two-week sampling periods over a span of 13 months. The demography of the sample was obtained from face-to-face questionnaire surveys with the households’ respondents. Subsequent data refinement resulted in a final sample of 219 households consisting of 4623 discrete measurements being used for statistical analysis in the IBM SPSS software package. Results of statistical analyses show that weighted average age has a small and positive but statistically insignificant correlation to average daily per capita HSW arising. It was also determined that older households possessed a slightly higher albeit statistically insignificant rate of per capita HSW generation compared to younger ones. Additionally, households with elderly residents were found to produce more HSW per capita. Households with toddlers discharged HSW at a comparable rate to households without. Likewise, households with toddlers exclusive of elders have similar rates of HSW arising to their counterparts. In conclusion, there is evidence to suggest that a positive linkage between age and the rate of HSW arising exists. However, evidence from this study shows that the relationship between the two is insignificant from a statistical perspective.